Proanthocyanidins isolated from the leaves of Ficus glomerata evaluated on the activities of rumen enzymes: in vitro and in silico studies - Lata, Suman; Koli, Pushpendra; Singh, Sultan; Bhadoria, Brijesh Kumar; Chand, Umesh; Yadav, Dinesh Kumar; Al-Shuwaili, Thamer; Ren, Yonglin (Frontiers in Chemistry, 2024)
Two new proanthocyanidins (2S:3S)-(-)-epicatechin-(4α→8)4-(2R:3R)-(+)-catechin (Compound 1) and (2R, 3R)-3-O-galloyl-(+)-catechin (4β→8)3-(2R, 3R)-3-O-galloyl-(+)catechin (Compound 2) were isolated from Ficus glomerata and characterized by ultraviolet spectroscopy (UV), proton nuclear magnetic resonance ( 1 H NMR), 13 C NMR and heteronuclear multiple bond correlation (HMBC). The bioactivity and drug score of isolated compounds were predicted using Osiris property explorer applications with drug score of 0.03 (Compound 1) and 0.05 (compound 2). Predictive drug scores provided an indication of the compounds' potential to demonstrate desired biological effects. Furthermore, the newly discovered proanthocyanidins tend to interact with protein due to their chemical structure and molecular conformation. Withthe aim of maintaining this focus, compounds 1 and 2 were subjected to in vitro testing against ruminal enzymes to further explore their potential impact. Both compounds showed significant inhibition activities (p < 0.01) against glutamic oxaloacetic transaminase in both protozoa and bacterial fractions, with an effective concentration (EC50) of 12.30-18.20 mg/mL. The compounds also exhibited significant inhibition (p < 0.01) of ruminal glutamic pyruvic transaminase activity, with EC50 values ranging from 9.77 to 17.38 mg/mL. Furthermore, the inhibition was recorded in R-cellulase in between EC50 value of 15.85 and 23.99 mg/mL by both compounds. Additionally, both compounds led to a decrease in protease activity with increasing incubation time and concentration. In conclusion, the results indicate that these novel proanthocyanidins hold the potential to significantly impact rumen enzyme biology.Furthermore, their promising effects suggest that they could be further explored for drug development and other important applications.